Impacts of Internet-Based Interventions for Veterans With PTSD: A Systematic Review and Meta-Analysis - Zhou, Yang; Bai, Zhenggang; Wu, Wei; Fan, Zijia; Wu, Cuiying; Li, Longyi; Li, Siyu (Frontiers in Psychology, 2021)
Background: Veterans who did not seek and complete treatment as intended have been shown to have an elevated risk of experiencing and being exposed to post-traumatic stress disorder (PTSD). Internet-based interventions (IBI) are regarded as potential treatments to reduce PTSD in veterans. However, the effects of IBI for veterans with PTSD are uneven. Objectives: IBI is defined as any internet-based series of psychosocial interventions, among which the internet works as a way of delivery. This study aimed to: 1) examine the effects of IBI on veterans’ PTSD outcome, 2) distinguish the elements of IBI that play an important role for veterans with PTSD. Methods: Web of Science, PubMed, EMBASE, PsycINFO, Cochrane, Wanfang Data, CNKI, and CQVIP databases were searched for RCTs in IBI programs for veterans with PTSD, covering all studies in English and Chinese published from January 1990 to November 2020. All processes followed PRISMA. Risk of bias of the studies was assessed by the Cochrane Systematic Review Handbook. The confidence of outcomes of this review was valued according to GRADE. Results: A total of 1,493 citations were identified after initial searching. Eventually, six RCT studies met the inclusion criteria. Beneficial effects of IBI were found on the overall PTSD outcome. Particularly, IBI based on CBT with peer support was found effective. The subgroup analysis demonstrated that scores of PTSD outcome measured by a PCL decreased an average score of 0.38. The intervention had a positive effect on PTSD outcome on veterans with comorbid psychological disorders. Overall, the six studies that were included were evaluated with low risk of bias, and the outcomes of meta-analysis were proved with high confidence. Conclusion: IBI have a positive effect on the overall PTSD outcome of veterans. The results encouraged us to focus on IBI with CBT with peer support for veterans, on specific instruments for veterans with PTSD, and on veterans with comorbid psychological disorders. In future, more high-qualified research and diverse cultural background of RCTs is needed to prove the effectiveness of IBI on veterans with PTSD.